The Narrative Art of Contemplator: An Analysis on Milan Kundera’s Works - Ma Feng (Bina Nusantara University, 2009)
Article presented a narrative theoretical analysis on Milan Kundera’s works. Its emphasis point lied on the unity of the theory and the practical explanation to the text. Kundera’s works joined the unique ponder art and the narrative artistic together, which had led to the work a possible implication that would be much richer. Based on a macroscopic angle, this article used the relative theory, including theories on classic and latter classic narrates study. Then, based on the microscopic angle, this article mainly utilized the narrative theory about “the intervention” as well as the acceptable aesthetic theory. What’s more, the article did not only carry on a careful narrative analysis on Kundera’s creation, but also discussed the profound effect with which the narration brought. This article offered some careful and profound discussions respectively on the narrator’s and reader’s intervenes. The narrator intervenes stressed that the narrator’s “narration person, narration method and the narration identity” in the work, and discussed the narrator “we”, illusion narration, parenthesis replenishment narration as well as the Polyphony and reliability which were brought by the narration method and narrator’s identity. The reader intervene stressed the reader’s strategy during the connoisseurship and the acceptance process, and also evaluated reader’s identity during the reading process, and concerned about the lost readers in the “garden paths phenomenon and jungle for explanation”.